2016
DOI: 10.1007/s00701-015-2687-y
|View full text |Cite
|
Sign up to set email alerts
|

"Clip first" policy in management of intracranial MCA aneurysms: Single-centre experience with a systematic review of literature

Abstract: Although this study has its inherent limitations, the effect brought about by microsurgical clipping of MCA ANs remains superior to that of endovascular embolisation and it should be sustained as the first treatment choice. The decision about the treatment strategy should be made by a multi-disciplinary team consisting of specialists from both teams, bearing in mind the higher occlusion rate and longevity of the surgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 73 publications
1
18
0
1
Order By: Relevance
“…Aneurysm size and location also dictate intervention, with middle cerebral artery aneurysms treated with clipping based on better patient outcomes than with coiling. 11,18,27,29,30 Our study demonstrated no significant adjusted odds of ARF in the CACo cohort, although this could be due to pertinent complications of iodine contrast-induced nephropathy in high-risk patients with renal disease. 5,26 Thus, is it possible that patients with renal disease were preferably treated with CAC.…”
Section: Discussionmentioning
confidence: 52%
“…Aneurysm size and location also dictate intervention, with middle cerebral artery aneurysms treated with clipping based on better patient outcomes than with coiling. 11,18,27,29,30 Our study demonstrated no significant adjusted odds of ARF in the CACo cohort, although this could be due to pertinent complications of iodine contrast-induced nephropathy in high-risk patients with renal disease. 5,26 Thus, is it possible that patients with renal disease were preferably treated with CAC.…”
Section: Discussionmentioning
confidence: 52%
“…In response to recent series of endovascular treatment of ruptured MCA aneurysms, several authors have reported their institution's results of a "clip-first" policy for MCA lesions. 19,24 In a series of 282 ruptured MCA aneurysms treated with microsurgical clipping, Rodríguez-Hernández et al 19 reported good outcomes (mRS scores 0-2) in 70.2% of these patients. This finding is comparable to the results in our series.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, rates of procedure-related mortality and morbidity were reported as 0.6%-5% for surgical clipping by the standard pterional approach for unruptured MCA aneurysm. 7,15,19,23,29 For unruptured MCA aneurysms less than 12 mm in diameter, the surgical morbidity of the standard pterional approach was 0%-0.6%. 19,23 These findings show that the neurological outcomes of our pteri- onal keyhole technique for unruptured MCA aneurysms are not inferior to those of the standard pterional approach.…”
Section: Discussionmentioning
confidence: 99%